Clinical implications of drug‐induced liver injury in early‐phase oncology clinical trials. Issue 22 (18th August 2020) - Mondaca, Sebastian P.; Liu, Dazhi; Flynn, Jessica R.; Badson, Sandy; Hamaway, Stefan; Gounder, Mrinal M.; Khalil, Danny N.; Drilon, Alexander E.; Li, Bob T.; Jhaveri, Komal L.; Schram, Alison M.; Kargus, Katherine E.; et al.
Abstract : Background: Data on drug‐induced liver injury (DILI) and acute liver failure (ALF) in modern phase 1 oncology trials are limited, specifically with respect to the incidence and resolution of DILI and the safety of drug rechallenge. Methods: This study reviewed all patients who were recruited to phase 1 oncology trials between 2013 and 2017 at Memorial Sloan Kettering Cancer Center. Clinicopathologic data were extracted to characterize DILI, and attribution was assessed on the basis of data prospectively generated during the studies. Logistic regression models were used to explore factors related to DILI and DILI recurrence after drug rechallenge. Results: Among 1670 cases recruited to 85 phase 1 trials, 81 (4.9%) developed DILI. The rate of DILI occurrence was similar for patients in immune‐based trials and patients in targeted therapy trials (5.0% vs 4.9%), as was the median time to DILI (5.5 vs 6.5 weeks; P = .48). Two patients (0.12%) met the criteria of Hy's law, although none developed ALF. The DILI resolved in 96% of the patients. Pretreatment factors were not predictive for DILI development. Thirty‐six of the 81 patients underwent a drug rechallenge, and 28% of these patients developed DILI recurrence. Peak alanine aminotransferase during the initial DILI was associated with DILI recurrence (odds ratio, 1.04; 95% confidence interval, 1.0‐1.09; P = .035). Conclusions: In modern phase 1 oncology trials, DILI is uncommon, may occur at any time, and often resolves with supportive measures. Rechallenging after DILI is feasible; however, the high rate of DILI recurrence suggests that clinicians should consider the severity of the DILI episode and treatment alternatives. Abstract : In modern phase 1 oncology trials, drug‐induced liver injury (DILI) is uncommon and may occur at any time. Drug rechallenge after DILI is feasible; however, the high rate of DILI recurrence suggests that clinicians should consider the severity of the DILI episode and other treatment alternatives.